2017
DOI: 10.1080/15374416.2017.1295381
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Advice and Children’s Bystander Behaviors During Bullying Incidents

Abstract: Many bullying prevention programs take a bystander approach, which encourages children to intervene when they are bystanders to bullying incidents. Little is known about how caregivers' advice to children might promote or undermine the positive bystander behaviors targeted by these programs. Accordingly, the aim of the current study was to investigate relations between caregivers' advice and children's bystander behavior during bullying situations. Participants were 106 racially/ethnically diverse 4th- and 5th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…It is well established that girls intervene in bullying situations more frequently than boys (Espelage, Green, & Polanin, ; Hawkins, Pepler, & Craig, ; O'Connell et al, ). This finding combined with the results of the study by Grassetti and colleagues suggesting that bystander children follow their parents' advice about how to respond to bullying (Grassetti et al, ) suggests that parents may suggest intervention during bullying more frequently to girls than boys. This hypothesis is consistent with evidence that parents implicitly and explicitly socialize the prosocial development of boys and girls differently (Mesman & Groeneveld, ); for example, parent encourage prosocial behaviors more frequently in infant girls than infant boys (Power & Parke, ).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…It is well established that girls intervene in bullying situations more frequently than boys (Espelage, Green, & Polanin, ; Hawkins, Pepler, & Craig, ; O'Connell et al, ). This finding combined with the results of the study by Grassetti and colleagues suggesting that bystander children follow their parents' advice about how to respond to bullying (Grassetti et al, ) suggests that parents may suggest intervention during bullying more frequently to girls than boys. This hypothesis is consistent with evidence that parents implicitly and explicitly socialize the prosocial development of boys and girls differently (Mesman & Groeneveld, ); for example, parent encourage prosocial behaviors more frequently in infant girls than infant boys (Power & Parke, ).…”
Section: Introductionmentioning
confidence: 63%
“…It is surprising that little work has examined parental advice to bystander children, given that many bullying prevention programs are bystander‐oriented, parents play an important role in these programs, and advice‐giving is a common and salient way that parents socialize their children's peer behavior. One recent study demonstrated that children generally respond as bystanders to bullying in ways that their parents have advised them to respond (Grassetti et al, ). In that study, children were more likely to intervene when their parents advised intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As education professionals increasingly recognize the importance of facilitating bystander orientation to stop bullying and prevent future instances of aggression (Grassetti et al, 2018), researchers have begun to examine predictors of bystanders' willingness to intervene (Jenkins & Nickerson, 2017. In "School Connectedness and Bystander Intervention: The Moderating Role of Perceived Exclusion and Privilege among African American Students, " Knox et al (2021) highlights the importance of recognizing that predictors of bystander intervention may look different in various groups of students.…”
Section: Centering Race and Ethnicity In School Safetymentioning
confidence: 99%
“…Within the home setting, parent teachings to their children of prosocial antibullying responses received from school resources can communicate a variety of options to decrease the frequency of bullying. Research has indicated that youth adopt from their parents recommended bystander interventions when at school (Grassetti et al, 2018). Consequently, greater correspondence on bystander responses from parents and school staff can increase student confidence in immediate and consistent intervention when victimization is experienced or observed.…”
Section: Practical Implicationsmentioning
confidence: 99%